Inter-Semiotic Translation: Shakespeare on Screen - Weissbrod, Rachel (The Journal of Specialised Translation, 2006)
Cinematic adaptations of Shakespeare’s plays have been an important part of the history of cinema from its earliest days. The volume of research dealing with these adaptations is immense and keeps growing. The present article attempts to approach the subject from a translation studies perspective. Starting with Jakobson’s conception of “inter-semiotic translation”, it draws on Even-Zohar’s transfer theory and Holmes’ assumptions regarding the translation of texts created in the past. Combining research dealing with the relations between cinema and theatre in general and cinematic adaptations of Shakespeare’s plays in particular, it offers a framework for dealing with two questions: (a) How do cinematic adaptations of Shakespeare’s plays manoeuvre between the theatre and the cinema, two distinct media which use different semiotic languages and rely on different repertoires? (b) How do they handle the gap between the 16 th century and the time of their production?